The impact of education technology on students’ engagement and writing skills in higher education: A thematic review - Sanjida Alam Orpa; Md. Arfan Khan Sohan (Journal of Research in Instructional, 2026)
Education technologies influence the extent and type of student engagement in varying behaviors, learning engagement, and writing development, although the available research is limited. The cognitive, emotional, and ethical implications surrounding technology remain under-researched, despite the increasing volume of recent studies in higher education on this topic. This study examined the impact of digital learning settings and technology on how post-secondary educators enhance their students' engagement and writing skills. Thematic analysis was employed to identify patterns in the data and to analyze it. A thematic review approach was employed with 59 peer-reviewed studies published between 2004 and 2025.  The analysis of studies used a systematic inclusion/exclusion approach to research the dimensions of engagement (e.g., behavioral, cognitive, emotional, and social) and the role of technology. The study found that AI instructors, as well as collaborative platforms and widgets (e.g., multimedia), support cognitive and behavioral engagement. Grammarly and Google Docs foster metacognition, peer collaboration, and real-time feedback. However, some believe that excessive reliance on AI and digital distractions could inhibit creativity and critical thinking. Finally, technology affords personalized and interactive learning; therefore, it must be thoughtfully and ethically implemented, as this study suggests. Future studies should pay detailed attention to the longer-term impact of utilizing socially productive educational technology, educator preparedness, and equitable access for all students.